Backyarding : Theory and Evidence for South Africa - Brueckner, Jan K.; Rabe, Claus; Selod, Harris (World Bank, Washington, DC, 2018)
This paper explores the incentives for backyarding, an expanding category of urban land-use in developing countries that has proliferated South Africa. The theoretical model exposes the trade-off faced by the homeowner in deciding how much backyard land to rent out: loss of yard space consumption in return for a gain in rental income. Under common forms for preferences, the homeowner's own-consumption of yard space falls as land rent increases, causing more land to be rented to backyarders. With better job access for backyarders raising land rent by increasing their willingness-to-pay, the analysis then predicts that the extent of backyarding will be higher for parcels with good job access. This hypothesis is tested by combining a satellite- based count of backyard dwellings per parcel with job-access data. The empirical results strongly confirm the prediction that better job access increases the extent of backyarding.